СИНТАКСИЧЕСКИЙ УРОВЕНЬ ЭМОЦИОНАЛЬНОЙ РЕЧИ МУЖЧИН И ЖЕНЩИН В АНГЛИЙСКИХ АНЕКДОТАХ - ГаспарянС.К., Князян А.Т. (Studia Philologica, 2014)
The article highlights the syntactical aspect of males and females emotional speech in English anecdotes. The most frequently used syntactic means that create the appropriate humoristic effect contributing to vivid originality in anecdotes and attract listener’s attention are repetitions and elliptical constructions used by males and females to emphasize a particular word, phrase, idea or to give the anecdote a beat and a rhythm. Multiple research studies on syntax used by men and women reveal differences stemming from gender specific styles of “talk”.